Efeito de glyphosate sobre características produtivas em cultivares de soja transgênica e convencional - Melhorança Filho, André Luiz; Martins, Dagoberto [UNESP]; Pereira, Maria Renata Rocha [UNESP]; Espinosa, Wilhian Rodrigo (My University, 2010)
The aim of this work was to evaluate the grain yield of two soybean cultivars (CD-216 and CD- 212RR, divided into three stages: (i) to evaluate the effect of components of production, of simulated drift of glyphosate throught subdoses (1,3; 2,6; 5,3; 11,5 and 22,5 g e. a. ha-1) of two cultivars; (ii) to evaluate the influence of glyphosate (720; 1080; 1440 and 1800 g e.a. ha-1) in the transgenic soybean yield The experiments carried out in experimental area in the school farm of Uniderp, city of Dorados, MS ina typical Rhodic Haplustox. The experimental design used was in blocks to perhaps The parameters were: heigh oh the pln\ant, number of pods per plants, number of seeds per pod, masss of 100 grains, grain yield (%) of germination, dry mass of seedling, the lengh of radical and air part. The cultivate CD-212RR was not influenced by the subdoses application of glyphosate. Effect of growth stimulus was not observerd due to application of glyphosate subdoses in both cultivars in field conditions. Doses from 11,25 g e.a.ha-1 caused60 of phytotoxicity in CD-216, at 28 DAA reduce production by 33%. The height and number of pods per plant of cultivar CD- 212RR have been reduced and productivity decrease 21% with the application of 1.800 g e.a.ha-1 of glyphosate.
Effect of glyphosate on productive characteristics in conventional and transgenic soybean
Keywords: Glycine max; Glyphosate; Herbicide; Transgenic